MEDICAL FUZZY-EXPERT SYSTEM FOR PREDICTION OF ENGRAFTMENT DEGREE OF DENTAL IMPLANTS IN PATIENTS WITH CHRONIC LIVER DISEASE - Polishchuk, Vitaliy; Pavlov, Sergii; Polishchuk, Sergii; Shuvalov, Sergii; Dalishchuk, Andriy; Sachaniuk-Kavets’ka, Natalia; Mukhsina, Kuralay; Nazerke, Abilkaiyr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The paper presents an information technology for assessing the degree of engraftment of dental implants in the event of a pathology violation through the use of fuzzy sets, which allows using this method for medical diagnostic tasks. Main scientific results: developed algorithms and mathematical models that formalize the process supporting diagnostic decisions based on fuzzy logic; developed mathematical models of membership functions that formalize the presentation of qualitative and qualitative informational features based on the rules of fuzzy logic, which can be used in information expert systems when assessing the degree of engraftment of dental implants in case of disease with pathological diseases.